Review of the Macedonia’s first national communication under the United Nations Framework Convention on Climate Change - Ciconkov, Risto; Azievska, Maja (Macedonian Journal of Ecology and Environment, 2003)
Climate change, global warming and greenhouse effect is elaborated in this review. The measures and activities of the international organizations concerning climate change are presented as well as activities of the Republic of Macedonia. The process of preparation of First National Communication under the United Nations Framework convention on climate change is presented as well as its contents and basic principles.